Bounds on price-setting - Narayana Rao Kocherlakota (Theoretical Economics, 2021)
I study a class of macroeconomic models in which all firms can costlessly choose any price at each date from an interval (indexed to last period's price level) that includes a positive lower bound. I prove three results that are valid for any such half-closed interval (regardless of how near zero the left endpoint is). First, given any output sequence that is uniformly bounded from above by the moneyless equilibrium output level, that bounded output sequence is an equilibrium outcome for a (possibly time-dependent) specification of monetary and fiscal policy. Second, given any specification of monetary and fiscal policy in which the former is time-invariant and the latter is Ricardian (in the sense of Woodford 1995), there is a sequence of equilibria in which consumption converges to zero on a date-by-date basis. These first two results suggest that standard macroeconomic models without pricing bounds may provide a false degree of confidence in macroeconomic stability and undue faith in the long-run irrelevance of monetary policy. This paper's final result constructs a non-Ricardian nominal framework (in which the long-run growth rate of nominal government liabilities is sufficiently high) that pins down a unique stable real outcome as an equilibrium.
Keywords: E52; E61; E62; 330; Pricing bounds; monetary policy; fiscal policy